In utero therapy for congenital disorders using amniotic fluid stem cells. - Durrgah Latchumi Ramachandra; Sheng-Wen Steven eShaw; Sheng-Wen Steven eShaw; Panicos eShangaris; Stavros eLoukogeorgakis; Pascale V Guillot; Pascale V Guillot; Paolo eDe Coppi; Anna L David (Frontiers Media S.A., 2014)
Congenital diseases are responsible for over a third of all pediatric hospital admissions. Advances in prenatal screening and molecular diagnosis have allowed the detection of many life-threatening genetic diseases early in gestation. In utero transplantation with stem cells (IUT) could cure affected fetuses but so far in humans, successful IUT using allogeneic haematopoietic stem cells (HSCs), has been limited to fetuses with severe immunologic defects and more recently IUT with allogeneic mesenchymal stem cell transplantation, has improved phenotype in osteogenesis imperfecta. The option of preemptive treatment of congenital diseases in utero by stem cell or gene therapy are encouraging as it changes the perspective of congenital diseases. Thus, avoiding the need for post-natal treatment and reducing future costs. AFS have been isolated and characterized in human, mice, rodents, rabbit and sheep and can be a potential source of cells for therapeutic applications in a multitude of disorders that can be treated prenatally or postnatally. These cells have demonstrated the potential of repair in a range of disease models such as neurological disorder, tracheal repair, bladder injury and diaphragmatic hernia repair in adult or neonate stage. Several groups have shown the use of AFS in in utero therapy in rodents as well as sheep models. These results have been encouraging, thus allowing us to continue with the research and optimizing the procedures and experiments so as to allow it to be translated into clinic.